ANALISIS YURIDIS PEMALSUAN IDENTITAS OLEH PENJUAL KARTU SUBSCRIBER IDENTITY MODULE INTERNET - Sinambela, Winda Handayani; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The establishment of criminal law is expected to be able to overcome legalproblems that occur in society. The existence of criminal sanctions is expected to have adeterrent effect on the perpetrators. If you look into Indonesian criminal law, there is noregulation on identity falsification carried out in electronic media, so there is no sanctionto the perpetrators. If the regulation on counterfeiting is not regulated, there will be manycases of identity forgery using electronic media. So that the value of the identity willdecrease and will cause many other crimes. Adami Chazawi in his book